Komentarz do art. 22—23 ustawy z dnia 9 czerwca 2011 r. Prawo geologiczne i górnicze - Lipiński, Aleksander (Prawne Problemy Górnictwa i Ochrony Środowiska, 2020)
According to art. 22 of the GMA mining and geological licences, depending on the kind and place of the activity, are granted by the minister in charge of the environment, the head of the poviat or the marshal of the voivodship. The grant of the licence always must be preceded by cooperation with the authorities determined in art. 23 (like the President of National Atomic Energy Agency, the head of the local community, authorities responsible for the water management etc.). Depending on the kind of the licence or place of the activity, the „cooperating authorities” are consulting the draft of the licence (opinion) or the draft has to be agreed with them. Unfortunately, in most situations the premises determining results of such cooperation are very unclear. The result of such cooperation may be controlled by the administrative court.